2020
DOI: 10.21203/rs.3.rs-30583/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prognostic value of the ALBI grade among patients with single hepatocellular carcinoma without macrovascular invasion

Abstract: Background: Although evidence for the application of albumin–bilirubin (ALBI) grading system to assess liver function in hepatocellular carcinoma (HCC) is available, less is known whether it can be applied to determine the prognosis of single HCC with different tumor sizes. This study aimed to address this gap.Methods: Here, we enrolled patients who underwent hepatectomy due to single HCC from the year 2010 to 2014. Analyses were performed to test the potential of ALBI grading system to monitor the long-term s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…Gene transcription abnormalities associated with esophageal cancer, including chromosomal and tumour cell mutations, were a major research focus in the past [ 9 ]. Studies have shown that gene mutation is an important mechanism of esophageal cancer, and various genetic mutations are found in patients with esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Gene transcription abnormalities associated with esophageal cancer, including chromosomal and tumour cell mutations, were a major research focus in the past [ 9 ]. Studies have shown that gene mutation is an important mechanism of esophageal cancer, and various genetic mutations are found in patients with esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Isso se deve ao adequado manejo pré-operatório, com discussão multidisciplinar de todos os casos com indicação cirúrgica, e programação do procedimento a ser realizado de forma individualizada, evitando ressecções maiores em pacientes com maior risco de PHLF e considerando sempre a possibilidade de preservação de parênquima, especialmente em lesões de até 2 cm. Outros estudos também apontam que a presença de hipertensão portal (109) e de volumes residuais hepáticos menores que 20% a 25% se correlacionam com PHLF (110,111) .…”
Section: Discussionunclassified